Effect of cut-outs on the axial crushing response of cap and open-end hybrid frusta tube. (2020) - Patel, Vivek; Tiwari, Gaurav; Dumpala, Ravikumar
Highlights: Crushing performance of open and cap end hybrid frusta was explored. Effect of cut-outs and radial distance between hybrid frusta were investigated. Cut-out hybrid frusta showed lower PF and higher CLE. Cut-out hybrid frusta performed better compared to without cut-out hybrid frusta. The 4.44 mm radial distance hybrid frusta collapse in stable manner. Abstract: The present paper presents the computational analysis of the crushing response of AA-1080 cap and open end hybrid frusta tube, with and without circular cut-outs subjected to the quasi-static axial loading. The two concentric frusta tubes placed co-axially having different heights of 91.6 mm and 85 mm of inner and outer tubes respectively were considered as hybrid frusta. The frusta tubes thickness and semi-apical angle were assigned constant value as 1.15 mm and 5.71˚ respectively. The effect of radial distance (2.94 mm, 4.44 mm, and 6.94 mm) between two concentric tubes as investigated. The numerical simulations were carried out using finite element code LS-DYNA. The crushing behavior of hybrid frusta tubes was examined based on the response of the peak force (PF), mean force (MF), crush load efficiency (CLE), and energy absorbing capacity (EAC). The radial distance was found to have a major impact on the deformation behaviour and with an increase in radial distance, the CLE decreases. Moreover, the response of cut-outs on the performance of hybrid frusta was presented and analysed. Through having a cut-out on both sets of hybrid frusta, the CLE increased by 3% to 10% whereas the radial distance R3 was insignificant as per CLE perspective. Further, the reduction in PF was found 13% to 23% for cap end while 8% to 19% for open end hybrid frusta.